KONTRIBUSI ANREGURUTTA ABDURAHMAN AMBO DALLE DALAM KAJIAN HADIS DI INDONESIA - Rauf, Rusmin Abdul (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2022)
This article aims to examine the thoughts of Anregurutta Abdurahman Ambo Dalle in the field of hadith and his contribution to the study of Indonesian hadith. AG Abdurahman Ambo Dalle is a famous scholar from South Sulawesi. He not only founded the DDI Educational Institute whose branches are spread throughout Indonesia, but he is also prolific in writing. This study found that one of his works is an Nukhbah al Mardiyah which he dedicated as a contribution to the Science of Hadith. This book consists of 3 volumes however, only two have been found. The first volume contains a collection of hadith, while the second volume is his response to the social phenomena that occurred in his time.